2008
DOI: 10.1303/aez.2008.97
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal genetic structure in Beijing populations of the grain aphid Sitobion miscanthi (Takahashi): an investigation using microsatellites

Abstract: The grain aphid Sitobion miscanthi (Takahashi) is a major pest of cereal crops in China. Sexual reproduction is rarely found in this species, and the reproductive strategy is expected to be reflected in the population genetic structure. Using five microsatellites, we analyzed four populations of S. miscanthi sampled during the 2005-2006 wheat season (from October to May) from a Beijing suburb. Substantial allelic diversity was found, with an average 9.8 alleles per locus, but there were only 45 five-locus geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…and secondary ( Glycine max ) hosts. Other studies with anholocyclic aphid species such as Sitobion miscanthi and Tuberculatus quercicola have described a lack of differentiation within the season (Wang et al , 2008; Yao & Akimoto, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…and secondary ( Glycine max ) hosts. Other studies with anholocyclic aphid species such as Sitobion miscanthi and Tuberculatus quercicola have described a lack of differentiation within the season (Wang et al , 2008; Yao & Akimoto, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…and secondary (Glycine max) hosts. Other studies with anholocyclic aphid species such as Sitobion miscanthi and Tuberculatus quercicola have described a lack of differentiation within the season (Wang et al, 2008;Yao & Akimoto, 2009). In the sweet-pepper field, only the samples of M. persicae collected early in the season exhibited a higher genotypic diversity than those from its associated weeds, which afterward was generally low (fig.…”
Section: Sexual and Asexual Lineages In Central Chilementioning
confidence: 88%
“…Those with re‐arranged karyotypes (Clones 61 and 34) share allele sizes at many loci with Asian specimens of S. miscanthi (Taiwan, see Wilson et al . 1999; Beijing area, Wang et al . 2008) and their identity as S. miscanthi is unequivocal.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the small number of genotypes present in Australia and New Zealand, the range of morphometric variation within Australasia may be limited regardless of the number of samples measured, although the species is much more genotypically variable in Asia (Wilson et al . 1999; Wang et al . 2008).…”
Section: Discussionmentioning
confidence: 99%
“…De Barro et al (1995b) and Vorburger (2006) found evidence of host races exhibiting high genetic structuring at the beginning of a growing season, and this genetic structuring diminished as the season progressed. Aphid populations collected immediately after winter exhibited seasonal change in genetic structure when compared to populations sampled before or after (Wang et al, 2008). Sunnucks et al (1997) reported that aphids exhibited rapid temporal genetic changes and low variation in population structure between sample sites (indicative of movement and population mixing), and Han & Caprio (2004) reported temporal genetic change in Helicoverpa virescens.…”
Section: Introductionmentioning
confidence: 99%